The effect of pre-sowing lupin-oat mixture treatment with ozone and a biological product on the productivity formation and product quality - Т. M. Morozova (Зерновое хозяйство России, 2021)
There have been presented the study results on the effect of pre-sowing seed ozonation of narrowleaf lupin (Lupinus angustifolius) and common oat on their germination energy, germination capacity, productivity and product quality. The study was carried out in the period from 2018 to 2020 in laboratory and field conditions of the Kostroma RIA, the branch of the FSBSI “Russian Potato Research Center named after A.G. Lorkh”. The purpose of the current study was to find out the efficiency of pre-sowing seed treatment with an ozone-air flow and treatment with a biological product for their germination energy, germination capacity, productivity and product quality. The objects of the study were the common oats variety ‘Yakov’ and the narrowleaf lupin variety ‘Belozerny 110’. The seeds of the lupin-oat mixture were ozonized at a dose of 5.0 mg/m3 for 15 minutes and 30 minutes using an RIOS-10(20)-0.5 ozonizer. For comparison, the seeds were treated with the biological product ‘Fitosporin-M’. Ultimately, there were identified the best parameters of the pre-sowing seed treatment of the lupin-oat mixture. On average, over the years of study, pre-sowing seed ozonation greatly improves the germination energy of agricultural crops on 4.8–8.3%, laboratory germination was improved on 3.0–5.0%. The largest green mass productivity of lupin-oat mixture during pre-sowing seed treatment for three years was 26.1 t/ha in the variant with an ozone dose of 5.0 mg/m3 for 15 minutes, which was more than control on 29.2%. In the variant with ozonation time increase to 30 minutes, the average productivity was 23.2 t/ha, which was 14.8% more than in the control. Pre-sowing seed ozonation contributed to dry matter increase on 14.2–19.0%; crude protein yield increased on 32.8–53.2%; crude protein percentage in grain increased on 14.1–16.8%; metabolizable energy increased on 3.7–5,1%; fodder units increased on 4.3–6.5% compared to control. When treating seeds with a biological product ‘Fitosporin-M’, the average productivity was 22.8 t/ha, which was on 12.9% more than control, an increase in dry matter was on 16.6%, an increase in crude protein yield was on 19.6%, an increase in crude protein percentage in grain was on 0.8%, an increase in metabolizable energy was on 1.9%, an increase in fodder units was on 1.0%.